1985
DOI: 10.1073/pnas.82.7.2096
|View full text |Cite
|
Sign up to set email alerts
|

One hundred base pairs of 5' flanking sequence of a vaccinia virus late gene are sufficient to temporally regulate late transcription.

Abstract: A vaccinia virus late gene coding for a major structural polypeptide of 11 kDa was sequenced. Although the 5' flanking gene region is very A+T rich, it shows little homology either to the corresponding region of vaccinia early genes or to consensus sequences characteristic of most eukaryotic genes. Three DNA fragments (100, 200, and 500 base pairs, respectively), derived from the flanking region and including the late gene mRNA start site, were inserted into the coding sequence of the vaccinia virus thymidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 31 publications
6
86
1
Order By: Relevance
“…However, the ATI promoter is more A/T-rich than the already well known VV late promoter sequences, perhaps explaining why ATI is so strongly expressed. Indeed, a gene coding for the 11K VV protein and carrying an A/T-rich promoter has been reported to be expressed strongly in VV-infected cells (Bertholet et al, 1985). Furthermore, expression of a gene coding for the 28K protein was greatly reduced following a point mutation from A to G in a run of eight As between -15 and -7 upstream of the structural gene (Weir & Moss, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ATI promoter is more A/T-rich than the already well known VV late promoter sequences, perhaps explaining why ATI is so strongly expressed. Indeed, a gene coding for the 11K VV protein and carrying an A/T-rich promoter has been reported to be expressed strongly in VV-infected cells (Bertholet et al, 1985). Furthermore, expression of a gene coding for the 28K protein was greatly reduced following a point mutation from A to G in a run of eight As between -15 and -7 upstream of the structural gene (Weir & Moss, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional analyses of viral polypeptides synthesized in infected cells have revealed at least two late gene subsets that can be defined temporally (Pennington, 1974;Ichihashi et aL, 1971). The fine structures of several early and late VV genes have been determined (Bertholet et al, 1985(Bertholet et al, , 1986Cochran et al, 1985;Plucienniczak et al, 1985 ;H~inggi et al, 1986;Rosel et al, 1986;Weir & Moss, 1987;Weinrich & Hruby, 1986;Niles et al, 1986;Earl et al, 1986), and comparison of nucleotide sequences upstream from these genes has revealed that VV promoters lack both eukaryotic and prokaryotic consensus sequences. Instead they have characteristic signals (Venkatesan et al, 1981(Venkatesan et al, , 1982Weir & Moss, 1983) recognized by VV RNA polymerase but not by the cellular RNA polymerase II (Puckett & Moss, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…1. First, the coding sequence for mouse NT-3 was amplified from cloned genomic DNA and inserted into the recombination plasmid 1 Ik-ATA-18 [33], downstream of the cloned promoter that normally regulates the expression of an abundant 3 I-kDa protein component of the wild-type vaccinia virion. In plasmid 11 k-ATA-NT-3, the chimeric promoter/NT-3 cassette is flanked by DNA sequences derived from the vaccinia virus thymidine kinase (tk) gene.…”
Section: Construction Of a Recombinant Vaccinia Virus Expressing Nt-3mentioning
confidence: 99%
“…The VV shuttle plasmid pKB3 contains part of the VV TK gene interrupted by a unique EcoRI restriction enzyme site adjacent to the P11 late promoter of the 11K VV protein (Sarov & Joklik, 1972;Bertholet et al, 1985;Esposito et al, 1988). The cDNA of clone p30-VD2 was subcloned into this EcoRI site (Fig.…”
Section: Cells and Virusesmentioning
confidence: 99%